Vascular Cognitive Impairment and Vascular Dementia: A Literature Review - Azka Fadila Latifa; Annisa Fitria Zahra AS; Muhammad Fatih Ma'ruf; Novad Sawelly; Dini Suryani; Herpan Syafii Harahap (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Vascular Cognitive Impairment and Dementia (VCID) is a spectrum of cognitive disorders associated with cerebrovascular disease and is a major cause of cognitive decline and dementia in older adults. This study aimed to review the etiology, risk factors, pathophysiology, diagnostic evaluation, and management of VCID to support early detection and appropriate intervention. A literature review was conducted using relevant scientific publications and clinical guidelines addressing VCID. The findings indicate that VCID develops through complex mechanisms involving chronic cerebral hypoperfusion, blood–brain barrier dysfunction, vascular inflammation, impaired brain fluid drainage, and neuronal injury. Major risk factors include advanced age, hypertension, diabetes mellitus, dyslipidemia, smoking, atrial fibrillation, and cardiovascular disease, which contribute to cerebrovascular damage and cognitive impairment. Diagnosis requires comprehensive cognitive assessment, particularly the Montreal Cognitive Assessment (MoCA), supported by magnetic resonance imaging (MRI) to identify vascular lesions and exclude other causes of cognitive decline. Management requires an integrated, multimodal approach involving vascular risk-factor control, appropriate pharmacological therapy, cognitive rehabilitation, physical activity, and family and caregiver support. In conclusion, VCID is a multifactorial disorder with substantial clinical and socioeconomic consequences. Early cognitive screening, optimal management of vascular risk factors, rehabilitation, and increased public awareness are essential to facilitate prevention, early diagnosis, and long-term care while slowing disease progression and improving quality of life.